KOMUNIKASI VERBAL ABUSE ORANG TUA PADA REMAJA: (Studi Deskriptif Konsep Diri Remaja Di Kecamatan Kerumutan Kabupaten Pelalawan) - Hevi Susanti; Nujanah (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
The phenomenon that lately occurs and entrenched in the environment of Indonesian society in general and in particular in the District of Kerumutan, Pelalawan Regency, which considers that talking harshly, berating, yelling, scolding, threatening to children is normal. But parents should be able to give good examples to children by using language or words that are good and right. This condition can occur where parents do not really understand and do not know that the verbal ability possessed by parents in communicating with children will be directly absorbed by children and form a sustainable behavior.Results Self-concept owned by teenagers in Kec. Kerumutan Kab. Pelalawan is influenced by significant others. Where, adolescent self-concept in Kec. Kerumutan Kab. Pelalawan is a negative self-concept that is the type of social comparison and Biased scannin. The negative self-concept of social comparision type is of the view that it is indeed like what is said by others so that the view of itself really looks irregular because the self-concept formed is influenced by others. While the negative self-concept is Biased scannin type. Shown from the attitude of adolescents that he tends to feel unliked by his parents and feel unnoticed. Reflected Appraisal states that a person's self-concept will be formed if he gets an award from someone else. Where, the giver of appreciation and the amount of appreciation received by a person will determine the degree of self-concept that is formed. Appreciation from people who are considered important to someone (significant others such as: parents, friends, relatives, etc.) also provide a very big influence on the development of self-concept.